Geochemical properties and environmental impacts of seven Campanian tephra layers deposited between 40 and 38 ka BP in the varved lake sediments of Lago Grande di Monticchio, southern Italy. (15th June 2015) - Wutke, Kristina; Wulf, Sabine; Tomlinson, Emma L.; Hardiman, Mark; Dulski, Peter; Luterbacher, Jürg; Brauer, Achim
Abstract: We present the results of new tephrostratigraphical and environmental impact studies of the 40–38 ka varved sediment section of Lago Grande di Monticchio (southern Italy). The sediments in this time zone are correlated with the Heinrich H4-stadial that occurred between Greenland Interstadials GI-9 and GI-8, and include the widespread Campanian Ignimbrite (CI, 39.3 ka) as a thick tephra layer in the middle of the H4 stadial. The CI in the Monticchio record is overlain by the Schiava tephra from Vesuvius, c. 1240 varve-years younger than the CI, and preceded by four tephras from small-scale eruptions of the Phlegrean Fields and by an Ischia-derived tephra. The four Phlegrean Field-derived tephras were deposited 600 varve-years or fewer prior to the deposition of the CI and show very similar major, minor, and trace element glass compositions to those of the CI. This close similarity in composition and age could compromise the accurate linking and synchronisation of palaeoenvironmental records in the central Mediterranean area. Microfacies analyses and μ-XRF core scanning were used to characterise primary and secondary depositional features of all seven tephra layers and to evaluate environmental and ecological responses after tephra deposition. Higher concentrations of tephra-derived material (mainly glass shards and pumices) in primary and reworked layers were detected by elevated K-counts in μ-XRF elemental core scans. Reworked tephra derives mainly from in-washing from the littoral zone and the catchment and occurs within five to 30 years, and up to 1240 varve years, after the deposition of thinner (1–5 mm) and thicker (5–230 mm) tephra fallout deposits, respectively. An obvious response of diatom population growth directly after the primary tephra deposition was observed for the thicker tephra layers (>1 mm) during the first 1–8 years after deposition of the primary deposit indicating that the additional input of potential nutrients (glass shards) temporarily affected the ecological lake system. Highlights: Four geochemically similar tephras occur within 600 years prior to the CI eruption. Re-deposition of tephra in Monticchio occurs up to 1240 years after primary deposition. Diatom populations show general growth 1–8 years after tephra deposition during H4. Onset of H4 is dated in three eastern Mediterranean records at c. 40, 100 cal yr BP. Onset of interstadial GI-8 occurs in Monticchio 1167 varve years after the CI eruption.